Atmospheric hydrodeoxygenation of bio-oil oxygenated model compounds: A review - Pourzolfaghar, Hamed; Abnisa, Faisal; Daud, Wan Mohd Ashri Wan; Aroua, Mohamed Kheireddine (Elsevier, 2018)
Hydrodeoxygenation (HDO) of various bio oil oxygenated model compounds in low H2 pressure has been discussed in this study. Because of the high yield of aromatic mixtures in bio-oil, they carry great potential for fuel efficiency. Nevertheless, due to its high viscosity, abundance of acid, and heteroatom contaminants, the bio-oil ought to be upgraded and hydrotreated in order to be applied as an alternative fuel. A continuous low H2 pressure HDO of bio-oil is favored as it could be simply integrated with conventional pyrolysis systems, functioning at low pressures, as well as supporting a flexible plan for serial processing in respective bio-refineries. Additionally, such a process is cheaper and safer in comparison with the high pressure set ups. This review meticulously elaborates on the operation conditions, challenges, and opportunities for using this process in an industrial scale. The operating temperature, the H2 flow ratio, the active site, and the catalyst stability are some important factors to be considered when it is intended to reach a high conversion efficiency for the HDO in low H2 pressure.